Echinococcosis in Pakistan: One Belt & One Road Initiative - Khan, Aisha; Simsek, Sami; Ahmed, Haroon (Wolters Kluwer Medknow Publications, 2018)
[Abstract Not Available]
Keywords: Echinococcosis; Pakistan; Alliance; One Belt & One Road